Originated From
AOL Search

What is the tangent equation for the function f(x)=(2x+3)^5, where x=-1?

Liked this question? Tell your friends about it

2 Answers

Order by
Oldest to Newest
Newest to Oldest
Votes

To get the equation of the tangent line you need to evaluate the derivative at x=-1 to find the slope m, and evaluate the function at x=-1 to find the intercept for y=mx+b.  The function (2x+3)^5 at x=-1 evaluates to 1.

Let u be 2x+3. The derivative of u^n is nu^(n-1) du/dx which is 5(2x+3)^4 times 2, which at x=-1 comes out to 5(1)(2) = 10.  If you didn't know that derivativative method then you could expand (2x+3)^5 and find the derivative of each term.

To find y=mx+b, we know m=10, and 1=10(-1)+b so b=11 and the tangent is y=10x+11.

It's been too long for me.

Gratitude as a discipline involves a conscious choice.....* Victims of circumstance owe it to fate. Victims of choice owe it to themselves.*One of the widest gaps in human experience is the gap between what we say we want to be and our willingness to discipline ourselves to get there.

Ask a Question... We'll forward it to people who know

More Questions

How do you do 2x + 3y = -1 on a coordinate plane?

The equation 2x + 3y = -1 can be turned into the standard form y = mx +b by subtracting 2x from both sides and dividing by 3 giving y = -2/3 x -1/3. That gives the slope as -2/3 and the intercept = -1/3. You can graph that by picking x=0 giving y = -1/3, and x = 1 gives y = -1. Connect those ...

What is (.5x 2)(2x)?

There's something missing after .5x, and I'm guessing that there should be a + sign. Use the distributive law a(b+c) = ab+ac to get (.5x+2)(2x) = x^2+4x.

How do I design a 2x3 banner?

why dont you just order a banner instead and design it any way you like for a cheap price .www.customsignbanner.com.

How do you solve 3/4(x+8)=1/2x+3.5

I hope that you mean: (3/4)*(X+8) = (1/2)*X + 3.5 If that is what you mean than: Multiply both sides by 4 to get (the puppose is to get rid of the fractions..... make life easier): 3*(X+8) = 2*X + 14 3X + 24 = 2X + 14 3X - 2X = 14 -24 X = -10